2018
DOI: 10.14744/semb.2017.69772
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the accompanying parkinsonism on rehabilitation in stroke patients

Abstract: P arkinson Hastalığı (PH), parkinsonizm bulgularıyla ortaya çıkan, genellikle 60 yaş civarında ortaya çıkan nörodejeneratif bir hastalıktır. Hastalığın ilk tanımı İngiliz hekim James Parkinson. [1] tarafından 1817 yılında 'Titreten Beyin Felci Üzerine Bir Çalışma' (An Essay on The Shaking Pal-sy) monografında yapılmıştır. Alzheimer Hastalığı'ndan sonra ikinci sıklıkta görülür. Parkinson Hastalığı'nın prevalansı 100.000'de 360 ve insidansı 100.000'de 18 olup tüm parkinsonizm olgularının %80'inden fazlasını oluş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have reported that stroke patients with PD experience longer hospitalization stays; higher rates of morbidities such as pneumonia, sepsis, and acute kidney injury; and increased mortality rates compared to those without PD [5, 44]. Deteriorated movements due to PD can negatively affect the outcome of rehabilitation in stroke patients [45]. Therefore, clinicians should be encouraged to screen for symptoms of PD in stroke patients to achieve early diagnosis, provide timely dopamine replacement therapy, and introduce early rehabilitation to stroke patients with disabilities to maintain quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that stroke patients with PD experience longer hospitalization stays; higher rates of morbidities such as pneumonia, sepsis, and acute kidney injury; and increased mortality rates compared to those without PD [5, 44]. Deteriorated movements due to PD can negatively affect the outcome of rehabilitation in stroke patients [45]. Therefore, clinicians should be encouraged to screen for symptoms of PD in stroke patients to achieve early diagnosis, provide timely dopamine replacement therapy, and introduce early rehabilitation to stroke patients with disabilities to maintain quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Deteriorated movements due to PD can negatively affect the outcome of rehabilitation in stroke patients [45]. Therefore, clinicians should be encouraged to screen for symptoms of PD in stroke patients to achieve early diagnosis, provide timely dopamine replacement therapy, and introduce early rehabilitation to stroke patients with disabilities to maintain quality of life.…”
Section: Ta B L Ementioning
confidence: 99%
“…Although there is no consensus in physiotherapy program, increasing evidence shows that physical activity has positive effects on motor (especially walking and balance) and non-motor symptoms through plasticity and improves quality of life, and it is recommended to start a rehabilitation program as early as possible. [ 5 ]…”
mentioning
confidence: 99%
“…Although there is no consensus in physiotherapy program, increasing evidence shows that physical activity has positive effects on motor (especially walking and balance) and non-motor symptoms through plasticity and improves quality of life, and it is recommended to start a rehabilitation program as early as possible. [5] The vagus nerve is one of the major elements of the parasympathetic nervous system and plays an important role in the regulation of the immune system as well as vegetative functions. [6] Vagus activation suppresses inflammation through a complex cycle, the cholinergic anti-inflammatory pathway.…”
mentioning
confidence: 99%
“…In addition, Parkinsonian symptoms occurred in other neurological disease may complicate the management of the disease. [2] Distinguishing between NPH and PD can present a challenge, particularly when the assessment concentrates primarily on gait and balance performance. [3] The utilization of sensor-based technologies for measuring gait and balance is becoming increasingly popular.…”
mentioning
confidence: 99%